Confessor towards contraception - Orzeszyna, Jan (Family Forum, 2010)
One of important moral problems that priests in confessional encounter is the question of using contraception. The Church has always taught us that contraception is anintrinsically evil action and moral offenses in this area are objectively speaking seriously sinful. There are such spouses who want to be faithful to the teachings of the Church, but they cannot meet their requirements. This is particularly true when there appear difficult and exceptional situations that disrupt the regularity of the intercourse, when natural family planning is hindered or seems to be impossible. A confessor, while meeting in the confessional Catholic spouses who experience difficulties in a sexual sphere, but who honestly want to keep the teachings of the Church, should give them advice which will gradually encourage them to move forward on their way to sanctity of their married life. Giving them advice, he should apply the pastoral law of gradualness which will make them aware that having the determination to break with sins and constant, though gradual aspiration to achieve full reunification with the requirements of Gods will, despite a moral decline, they are still on their way to God.